2006
DOI: 10.1021/tx0601307
|View full text |Cite
|
Sign up to set email alerts
|

cis-Terpenones as an Effective Chemopreventive Agent against Aflatoxin B1-Induced Cytotoxicity and TCDD-Induced P450 1A/B Activity in HepG2 Cells

Abstract: Aflatoxin B1 (AFB1) is a potent carcinogen, which can significantly increase the risk of hepatocellular carcinoma development through food contamination. In past decades, chemopreventive agents such as oltipraz and chlorophyllins have demonstrated that chemointervention is an effective approach to reduce the hepatotoxicity by AFB1. However, due to the potential adverse effects of these agents, alternative novel mechanism-based chemopreventive agents are needed. We report here that novel cis-terpenones 1-3, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The extract may also reduce the involvement of Ca 2+ dependent permeabilisation of renal cortex mitochondria as it has been shown that there is a possible involvement of Ca 2+ dependent permeabilisation of renal cortex mitochondria in cisplatin nephrotoxicity 19 . Anthocyanins are ubiquitous in the calyces of the plant thus this property of the extract may be attributed partly to these flavonoids which are known to be potent antioxidants and free radical scavengers 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract may also reduce the involvement of Ca 2+ dependent permeabilisation of renal cortex mitochondria as it has been shown that there is a possible involvement of Ca 2+ dependent permeabilisation of renal cortex mitochondria in cisplatin nephrotoxicity 19 . Anthocyanins are ubiquitous in the calyces of the plant thus this property of the extract may be attributed partly to these flavonoids which are known to be potent antioxidants and free radical scavengers 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Further work should focus on elucidating the actual protective mode of the extract. Since there are various phytochemicals in the calyces, proper fractionation of the extract should be done and each fraction subjected to both in vitro and in vivo studies since some notable bioactivities of terpenes have also been reported 25 in addition to the fact that flavonoids also possess pro-oxidant activities 26 . Progress in this area will also extend the borders of even cisplatin chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…OHCT, like artemisinin, rapidly kills the early ring stage in vitro , suggesting that it could be used in combination with a slow-acting drug, such as chloroquine. The previous demonstrations that OHCT inhibits human liver cytochrome P450 3A4 [ 8 , 9 ] further suggests that it may reduce metabolism of anti-malarial compounds, such as artemisinin, that are metabolized by this enzyme [ 11 ], thus increasing the half-life and rendering them more effective. The inhibition of human liver cytochrome P450 3A4 by OHCT was shown to be mixed competitive inhibition indicating that OHCT was binding at a site different from the active site [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of HCT and OHCT was described previously [ 7 , 8 ]. It was previously shown that OHCT protects human liver cells against aflatoxin and inhibits activity of liver microsomal cytochrome P450 3A4 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples are the terpenoids β-pinene, oct-1-en-3-ol, β-caryophyllene, octan-3-ol, and E, E-αfarnesene ( Figure 2) (Eyele et al, 2006). Dietary polyphenols, carotenoids and terpenes have exhibited significant medicinal potentials (Wang et al, 2008;Zhou et al, 2006). The observed effects of S. monostachyus could be ascribed to these antioxidant phytochemicals which acted in synergy.…”
Section: Variablementioning
confidence: 99%